Development and validation of four ferroptosis-related gene signatures and their correlations with immune implication in hepatocellular carcinoma - Zhang, Ying; Ren, He; Zhang, Chunting; Li, Haihua; Guo, Qingzhi; Xu, Haitao; Cui, Lina (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC) is one of the most common malignant tumors. This tumor presents with an insidious onset, rapid progression, and frequent recurrence. Ferroptosis is a newly discovered mode of programmed cell death that may play a key role in the progression of HCC. This study aimed to investigate the prognostic value of ferroptosis-related genes (FRGs) in HCC and their impact on tumor immune function, thereby providing new insights into targeted therapy for HCC. First, 43 differentially expressed FRGs were identified using the TCGA database, and four prognostically relevant methylation-driven FRGs (G6PD, HELLS, RRM2, and STMN1) were screened via survival and methylation analyses. Gene co-expression, mutation, and clinicopathological characterization indicated that these four pivotal FRGs play essential roles in tumor progression. We also validated these four genes using transcriptomic and proteomic data as well as cohort samples from our patients. Moreover, receiver operator characteristic (ROC) curves confirmed that the signatures of the four FRGs were independent prognostic factors in HCC. Gene set enrichment analysis of the four FRGs showed statistically significant associations with pathways related to HCC proliferation. Finally, the TIMER and TISIDB databases indicated that the four FRGs were statistically significantly correlated with tumor-infiltrating immune cells and immune checkpoint expression. Taken together, this study provides information guiding a novel therapeutic strategy targeting FRGs for HCC treatment.